The art of Mondo - Bird, Brad, 1957-; League, Tim (San Rafael, California : Insight Editions, 2017)
Experience the incredible pop culture art of Mondo, beloved by fans and iconic filmmakers alike. Based in Austin, Texas, Mondo is an art gallery and online store devoted to the love of film, art, music, and collectibles. Over the years, the company has received global recognition for its incredible art posters that bring to life classic films, television shows, and comics in a refreshing and utterly striking new way, offering a unique perspective on everything from Star Wars to Robocop , Back to the Future , Jurassic Park , Game of Thrones , Godzilla , Kill Bill , and many, many more. For the first time, The Art of Mondo brings together this highly sought-after art in one deluxe volume that showcases the incredible ingenuity of the studio's diverse stable of artists whose vastly different styles are united by one guiding principle: limitless passion for their subject matter. Adored by the creative talents to whom Mondo's art pays tribute--including Paul Thomas Anderson, Guillermo del Toro, Zack Snyder, Quentin Tarantino, and Edgar Wright, to name but a few--this richly imaginative work is fueled by a love of pop culture that fans recognize and identify with, giving Mondo's output a rare and valuable synergy with its audience. While these posters are normally produced in a limited quantity and sell out in minutes, The Art of Mondo allows fans to explore the studio's remarkable back catalog, including Olly Moss's iconic Star Wars trilogy work, Laurent Durieux's brilliantly subtle Jaws poster, and Tyler Stout's evocative Guardians of the Galaxy art. Other key Mondo artists such as Jock, Martin Ansin, and Aaron Horkey will also feature. Definitive, visually stunning, and filled with art that celebrates some of the biggest and best-loved properties in pop culture, The Art of Mondo is the ultimate book for cult art fans everywhere.
Keywords: Mondo (Firm : Austin, Tex.); Film posters -- Pictorial works